In vitro regeneration system of teak (Tectona grandis L.) - Lim, Sooi Ping; Aziz, Maheran Abdul; Sinniah, Uma Rani; Zainudin, Fadhilah (Penerbit Universiti Sains Malaysia, 2004)
Tectona grandis, commonly known as teak, is a member of the Verbanaceae family. It is one of the world’s premier appearance grade timbers and is highly sought after for its attractiveness, durability and resistance to termite and fungal infection (Appanah and Weinland, 1993).